Pembentukan "KIPAS: Kelompok Ibu Pintar, Anak Sehat" bersama Ibu-ibu Pengurus Cabang 'Aisyiah Umbulharjo - Ingenida Hadning; Nurul Maziyyah; Aji Winanta; Indriastuti Cahyaningsih; Indra Putra Taufani (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Umbulharjo is the sub-district with the worst nutritional disaster in Yogyakarta City in 2020, with 37 children. Mother becomes an important figure who plays a role in family health. PCA Umbulharjo is one of the organizations that shelter mothers with various educational backgrounds, but are still lay about health problems. Therefore, this service program aims to provide education and training related to health and balanced nutrition for families. This service program was implemented on March 6, 2022 with 37 members of PCA Umbulharjo with presentations on materials related to the Gerakan Masyarakat Hidup Sehat (GERMAS) and balanced nutrition for families, then continued with training on making children's lunches (bento) and closed with the handover of funding and books related to making menus with balanced nutrition to partners. The age of the participants was 46-55 years (46%). The effectiveness of the implementation of activities was assessed by pretest and posttest. There was an increase in the average score of the participants from the pretest 79.39 to 92.12 in the posttest with a value of p = 0014, so it can be said that this activity is effective in increasing participants' understanding. Assistance to PCA Umbulharjo mothers needs to be carried out routinely to implement GERMAS and provide nutritional menus for families, so that they can help improve poor nutritional status in toddlers, especially in Umbulharjo sub-district.